If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -8 = 9x + -5 Reorder the terms: -8 + 10x = 9x + -5 Reorder the terms: -8 + 10x = -5 + 9x Solving -8 + 10x = -5 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -8 + 10x + -9x = -5 + 9x + -9x Combine like terms: 10x + -9x = 1x -8 + 1x = -5 + 9x + -9x Combine like terms: 9x + -9x = 0 -8 + 1x = -5 + 0 -8 + 1x = -5 Add '8' to each side of the equation. -8 + 8 + 1x = -5 + 8 Combine like terms: -8 + 8 = 0 0 + 1x = -5 + 8 1x = -5 + 8 Combine like terms: -5 + 8 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 458000*8= | | -16=-3p+p | | 449000*8= | | 3n=4n-4 | | 8n+3n=-22 | | 2x+26=44 | | 2x+10=x+36 | | 35-14=-35 | | 96+x=40x | | 5x+100=-235 | | -6s=36 | | y=(1-x)/1.2 | | (x+7)(x-2)=(x+1)(x+1) | | 1.4(x+1.2)=7.8 | | -24/5=31/2h | | (x+7)(x+2)=(x+1)(x+1) | | m=z+bx | | 12x+8y+7x=z | | 2(3x-4)+6(x-5)=-3(4-5x)+5x-16 | | 4y-1x+2y=z | | [8+(-4)]-5= | | -8/12-21/12 | | 12+[-5+(-4)]= | | (7/x)-(1/7)=(2/x) | | 3(3x-2)=15 | | 2(3x-5)+6(x-3)=-3(3-5x)+5x-1 | | 2-4(x+3)=4-2(3x+5) | | 2.5=2/s | | -2(-3)-5y=4 | | -2y-42=3(y+1) | | -2/3(6*3-45)-2(3) | | 9x+2x=0x |